Gastroenteritis viruses - Estes, Mary (Henry Stewart Talks, 2007)
Viruses causing diarrhea, Epidemiology, Rotavirus pathogenesis, Rotavirus infection in calves, Rotavirus genes and proteins, Rotavirus replication, NSP4, Properties of rotavirus enterotoxin, Treatment and vaccines, Norovirus, Norovirus pathogenesis, Challenges studying Norwalk virus
Archived at 2018/05/31